PENGARUH MOTIVASI DAN BERBAGI PENGETAHUAN TERHADAP KINERJA KARYAWAN PT. HUTAMA KARYA INFRASTRUKTUR PROYEK PEMBANGUNAN JALAN TOL RUAS SIMPANG INDRALAYA – MUARA ENIM SEKSI SIMPANG INDRALAYA – PRABUMULIH ZONA 2-5 - Aziz Almeyda, Restadoni Muhammad; Mas’ud, Fuad (Diponegoro Journal of Management, 2024)
ABSTRACT The crucial aspect of managing organizational resources to achieve goals is through performance optimization. Currently, the success of an organization is closely linked to the optimal performance of the required human resources. Therefore, support for human resource dimensions, particularly employee performance, becomes a key element in achieving those goals. This research aims to analyze the influence of work motivation and knowledge sharing on the performance of employees at PT. Hutama Karya Infrastruktur. The method employed in this study involves data collection through a questionnaire with 150 respondents using purposive sampling technique. Data analysis in this research utilizes multiple linear regression analysis with SPSS Statistics 25. The results of this research indicate that work motivation (X1) has been proven to have a positive and significant impact on employee performance, providing an understanding that increased motivation can enhance employee performance. Meanwhile, knowledge sharing (X2) also has a positive and significant impact on employee performance. This means that an improvement in knowledge sharing practices can contribute positively to employee performance. The coefficient of determination shows that employee performance is influenced by work motivation and knowledge sharing at 0.258.